Reducing the Frequency of Rear Lamp Breakdown on the DT Coal Hauling Unit Arocs 4845 in the Mining Area of PT. Antareja Mahada Makmur Site PT Mifa Bersaudara Period (2024) - Yato Yato; Muhammad Hanif Iswanto; Tegar Tahanuji; Agus Sutiono; Yuli Adi Gunawan (Journal of World Science, 2025)
The high coal production target of PT Antareja Mahada Makmur at the PT MIFA Bersaudara jobsite demands the availability of optimal heavy equipment units. The Mercedes-Benz Arocs 4845 unit as the main means of transportation experienced a decrease in productivity due to frequent breakdowns in the rear lamps, which interfered with coal getting and coal hauling activities. This study aims to implement improvements to reduce the frequency and duration of breakdowns in the taillights of the DT Arocs 4845 unit. The method used was a direct experiment with several stages of technical intervention: (1) replacement of bulb lamps with more vibration-resistant LED types, (2) modification of lamp brackets with the addition of damper rubber and safety chains, and (3) repair of electrical wiring. Breakdown data before (April 2024) and after the repair (July 2024) were analyzed using Pareto charts and cost calculations. The implementation of the fix successfully eliminated the taillight breakdown incidents altogether. The frequency of breakdowns decreased from 12 times (21.18 hours lost) to 0 times, thus saving potential lost costs of IDR 31,742,518 per month. Integrated solutions for LED light replacement and bracket modification have proven to be very effective and efficient in improving unit reliability. This research provides a proactive maintenance strategy that can be replicated for similar units to support the achievement of production targets.